ERS International Congress 2022: highlights from the Thoracic Surgery and Lung Transplantation Assembly. Issue 2 (17th April 2023) - Magouliotis, Dimitrios E.; Bos, Saskia; Esendagli, Dorina; Nardini, Marco; Migliore, Marcello; Perch, Michael; Cardillo, Giuseppe; Meloni, Federica; Ricciardi, Sara; Hellemons, Merel
The thoracic surgery and lung transplantation assembly (Assembly 8) of the European Respiratory Society (ERS) is delighted to present the highlights from the 2022 ERS International Congress that took place in a hybrid version in Barcelona, Spain. We have selected the four main sessions that discussed recent advances across a wide range of topics including the effects of coronavirus disease 2019 on thoracic surgery and the challenges regarding lung transplantation in connective tissue diseases and common variable immunodeficiency. The sessions are summarised by early career members in close collaboration with the assembly faculty. We aim to provide the reader with an update and enhanced insight into the highlights of the conference in the fields of thoracic surgery and lung transplantation. The Thoracic Surgery and Lung Transplantation Assembly (Assembly 8) of the @EuroRespSoc is delighted to present an enhanced insight into the highlights from the 2022 #ERSCongress (Spain) https://bit.ly/3HED6Jj